FALSIFICATIONS OF THE ENERGY BALANCE EQUATION, PUASSON ADIABATS AND LAPLACE SOUND SPEED - K.B. Jakupov (Academic Scientific Journal of Computer Science, 2019)
The falsity of the energy balance equation with a specific heat capacity coefficient at constant pressure, the fake Poisson adiabat, and the fake Laplace formula of adiabatic sound velocity are established. Universal formulas of adiabatic ideal gas and sound velocity are proposed and substantiated. Bibl.10.